Culture Teaching In Foreign Language Education: Theoretical Foundations And Pedagogical Implications - Ghedeir, Brahim Mohammed (جامعة الوادي - University of Eloued, 2021)
The current research work focuses on an investigation carried out in the University of El- Oued, Algeria about EFL university teachers’ perceptions of their culture teaching practice as mediators of language and culture in the foreign language class. The study' s main purpose is to outline the main concepts, principles, and approaches regarding culture in English language teaching. This study focuses on what should be taught about culture in English language teaching. In order to achieve the above stated aims and objectives, a questionnaire targeting twenty English teachers was used as a data gathering tool. A multi-method approach that involved both quantitative and qualitative research methods is adopted in this research work project. Triangulation of sources and methods is also used in order to secure the validity and reliability of the research. The findings of this study serve as a guide in enhancing intercultural competence teaching in foreign language education.
Article
Keywords: Cultural communication ; Cultural understanding ; Culture teaching ; English language teaching ; Intercultural competence